1995
DOI: 10.1083/jcb.130.5.1161
|View full text |Cite
|
Sign up to set email alerts
|

Membrane/microtubule tip attachment complexes (TACs) allow the assembly dynamics of plus ends to push and pull membranes into tubulovesicular networks in interphase Xenopus egg extracts.

Abstract: Abstract. We discovered by using high resolution video microscopy, that membranes become attached selectively to the growing plus ends of microtubules by membrane/microtubule tip attachment complexes (TACs) in interphase-arrested, undiluted, Xenopus egg extracts. Persistent plus end growth of stationary microtubules pushed the membranes into thin tubules and dragged them through the cytoplasm at the ~20 p,m/ min velocity typical of free plus ends. Membrane tubules also remained attached to plus ends when they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 60 publications
6
77
0
Order By: Relevance
“…ER tubules and microtubules closely align over considerable distances and single-point attachment sites are evident at the light microscopic and ultrastructural levels (Baumann and Waltz, 2001). Video microscopy studies have revealed extension of ER tubules along microtubules during ER expansion in live cells and during reconstitution of the ER network from microsomes in cell-free systems (Terasaki et al, 1986;Dabora and Sheetz, 1988;Lee et al, 1989;Allan and Vale, 1991;Allan, 1995;Waterman-Storer et al, 1995;Waterman-Storer and Salmon, 1998). Interestingly, microtubule-dependent motility exclusively controls the rapid extension of ER tubules out to the cell periphery, whereas a slower movement of ER tubules towards the cell center is independent of microtubules (Terasaki and Reese, 1994;Waterman-Storer and Salmon, 1998).…”
Section: Microtubules Kinesin and Dynein In Er Movementmentioning
confidence: 99%
See 2 more Smart Citations
“…ER tubules and microtubules closely align over considerable distances and single-point attachment sites are evident at the light microscopic and ultrastructural levels (Baumann and Waltz, 2001). Video microscopy studies have revealed extension of ER tubules along microtubules during ER expansion in live cells and during reconstitution of the ER network from microsomes in cell-free systems (Terasaki et al, 1986;Dabora and Sheetz, 1988;Lee et al, 1989;Allan and Vale, 1991;Allan, 1995;Waterman-Storer et al, 1995;Waterman-Storer and Salmon, 1998). Interestingly, microtubule-dependent motility exclusively controls the rapid extension of ER tubules out to the cell periphery, whereas a slower movement of ER tubules towards the cell center is independent of microtubules (Terasaki and Reese, 1994;Waterman-Storer and Salmon, 1998).…”
Section: Microtubules Kinesin and Dynein In Er Movementmentioning
confidence: 99%
“…Microtubule-dependent ER movement results from the activity of microtubule-associated motors as well as the polymerization of microtubules (Dabora and Sheetz, 1988;Vale and Hotani, 1988;Dailey and Bridgeman, 1989;Waterman-Storer et al, 1995;Waterman-Storer and Salmon, 1998;Lane and Allan, 1999). Motors can either drag membranes along underlying microtubules or drive the sliding of membrane-associated microtubules, whereas microtubule polymerization can promote the movement of an ER tubule bound to the dynamic microtubule tip (Waterman-Storer and Salmon, 1998).…”
Section: Model a Model Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Waterman-Storer et al (1995) presented in vitro studies showing that membranes from Xenopus eggs are moved and positioned after selective attachment to the growing ends of microtubules. Whether such events occur in vivo is not yet known.…”
Section: Palmitoylation Of Tubulinmentioning
confidence: 99%
“…Before attaching to the microtubule plus end, the kinetochore attaches and glides rapidly along the wall of the microtubule (A, right). (After 10) A METAPHASE B METAPHASE (Mitchison et al, 1986;Wise et al, 1991) Evidence for Force Generation by Assembly/Disassembly of Microtubules In addition to governing microtubule length and inducing chromosomesto movetowards or away from the spindle pole in vivo, experiments performed on in vitro systems over the last few years clarify the situation further. They show that assembling and elongating microtubules can push, and that disassembling and shortening microtubules can pull, organelles and other loads (Figs.…”
mentioning
confidence: 99%